Synergistic effects of combined motor and language interventions on stroke rehabilitation: a holistic approach - Saber-Moghadam, Reihaneh; Zeinalzadeh, Afsaneh; Jamali, Jamshid; Farzadfard, Mohammad Taghi; Sobhani-Rad, Davood (Frontiers in Human Neuroscience, 2024)
Background: Stroke patients typically suffer from a range of symptoms, such as motor and language impairments, stemming from shared neural networks. The recovery process after stroke is intricate and requires a comprehensive approach. While previous studies have investigated the motor and language interventions separately, we aimed to explore the relationship between these domains and compared the effectiveness of individual interventions versus their combined use.: We divided 45 stroke patients into three groups: Group A received Speech and Language Therapy (SLT); Group B underwent Arm Ability Training (AAT); and Group C participated in a consecutive combination of SLT and AAT. Participants attended 40-minute sessions three days a week for three weeks. Standardized assessments, including picture naming test, sentence comprehension test, and hand dexterity test, were conducted pre-and post-treatment and during the first and second weeks of the intervention.Results: Within-group comparisons demonstrated a significant enhancement in test scores for all groups post-intervention compared to pre-intervention (P < 0.05). Between-group comparisons revealed significant differences (P < 0.05) in performance on the picture naming test during the first week, sentence comprehension test in the second week, functional rating subscale changes pre-and post-treatment and the first week, and the length of the time improvements from pre-intervention to the first week.Our findings highlight the mutual and synergistic benefits between motor and language functions. While SLT and AAT were found to be effective independently, their combined application yielded superior outcomes, emphasizing the holistic advantages of integrating these interventions in stroke rehabilitation.